2001
DOI: 10.1037/1082-989x.6.4.330
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inclusive and restrictive strategies in modern missing data procedures.

Abstract: Two classes of modern missing data procedures, maximum likelihood (ML) and multiple imputation (MI), tend to yield similar results when implemented in comparable ways. In either approach, it is possible to include auxiliary variables solely for the purpose of improving the missing data procedure. A simulation was presented to assess the potential costs and benefits of a restrictive strategy, which makes minimal use of auxiliary variables, versus an inclusive strategy, which makes liberal use of such variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
1,560
11
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,972 publications
(1,666 citation statements)
references
References 18 publications
29
1,560
11
17
Order By: Relevance
“…We have not reported results obtained by analysing only the complete cases because of the potential bias and loss of precision associated with the large proportion of missing income data; instead, we used multiple imputation. We imputed all missing data under a missing at random (MAR) assumption and adopted an inclusive strategy for the imputation model (31)(32)(33) .…”
Section: Discussionmentioning
confidence: 99%
“…We have not reported results obtained by analysing only the complete cases because of the potential bias and loss of precision associated with the large proportion of missing income data; instead, we used multiple imputation. We imputed all missing data under a missing at random (MAR) assumption and adopted an inclusive strategy for the imputation model (31)(32)(33) .…”
Section: Discussionmentioning
confidence: 99%
“…In other words, as long as the missing values of y on occasion i are not unique predictors of missingness for y on occasion i after controlling for observed values of y from previous time points or other predictors in the model (e.g., other within-subjects or between-subjects covariates), then the missingness is ignorable under maximum likelihood estimation, which will yield unbiased parameter estimates and standard errors (Schafer & Graham, 2002). Moreover, Collins, Schafer, and Kam (2001) recently demonstrated that in a variety of realistic missingness scenarios, the persistence of a unique relationship between scores on y and missingness on y can have a rather minor impact on parameter estimates and their standard errors. 3 We controlled for initial status and linear change in these models and equivalent models in Studies 2 and 3 because multivariate models that we ran with these data (Raudenbush, Brennan, & Barnett, 1995) within-person equations for evaluating simultaneously the association of anger or fear (the presumed mediators) and rumination (the predictor variable) with the TRIM variables (the outcomes) were of the form: (6) and we again included between-persons equations as in Equations 3-5 above.…”
Section: Statistical Models and Analysesmentioning
confidence: 99%
“…Specifically, all variables for the analysis model, including the outcome variable (Moons et al, 2006;StataCorp, 2013) should be included. A comparison of a "restrictive" (limited use of auxiliary) variables, and an "inclusive" (including many auxiliary variables) strategies clearly found the latter to be superior (Collins et al, 2001).…”
Section: Variables Used In Imputationmentioning
confidence: 98%
“…The benefits of MI in the face of NMAR data are not as predictable. However, it has been reported that MI is robust to the NMAR mechanism if the % of missing observations is <25% and the correlation between the cause of missingness and the variable subject to missingness was <.4 (Collins et al, 2001). …”
Section: Simulation Study -Based On Observed Missing Data Patternmentioning
confidence: 99%